2008
DOI: 10.1021/np800459d
|View full text |Cite
|
Sign up to set email alerts
|

Pancratium canariense as an Important Source of Amaryllidaceae Alkaloids

Abstract: Four new alkaloids (1-4) have been isolated from a methanolic extract of bulbs of Pancratium canariense, together with 12 known alkaloids (5-16). The structures of the new alkaloids were determined by extensive 1D and 2D NMR spectroscopic studies and X-ray diffraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 40 publications
3
17
0
Order By: Relevance
“…The SD (n = 2) in all cases were less than 15%. [29] b) [24] c) [28] d) [37] e) [38] f) [39] Investigation of the uptake of the carbon source of the nutrient medium showed that the degree of utilization of the sugars from L. aestivum line 80 shoot culture decreased with decreasing the temperature of cultivation from 26 • C to 18 • C (from 44.9% to 22.0%, Fig. 4A).…”
Section: Effects Of Temperature and Flow Rate Of Inlet Airmentioning
confidence: 99%
“…The SD (n = 2) in all cases were less than 15%. [29] b) [24] c) [28] d) [37] e) [38] f) [39] Investigation of the uptake of the carbon source of the nutrient medium showed that the degree of utilization of the sugars from L. aestivum line 80 shoot culture decreased with decreasing the temperature of cultivation from 26 • C to 18 • C (from 44.9% to 22.0%, Fig. 4A).…”
Section: Effects Of Temperature and Flow Rate Of Inlet Airmentioning
confidence: 99%
“…As part of our search for novel and bioactive compounds, we isolated three new Amaryllidaceae alkaloids, 5,6-dehydrodihydrolycorine (1), 6b-acetoxycrinamine (2), and (þ)-8-O-acetylhomolycorine a-N-oxide (3), together with eleven known analogs from bulbs of Lycoris radiata, a Chinese folk medicine famous for the treatment of poliomyelitis [15]. The new structures were elucidated by means of spectroscopic methods, and the known compounds were identified as 6-hydroxycrinamine (4) [16], homolycorine (5) [17], dihydrolycorine (6) [18], lycorine (7) [18], 7-oxodihydrolycorine (8) [19], (þ)-hippeastrine (9) [20], 2a-hydroxy-6-O-methoxyloduline (10) [21], galanthamine (11) [22], 7-deoxynarciclasine (12) [23], pancratinine C (13) [24], and 5,6-dihydrobicolorine (14) [25]. In addition, compounds 1 -3 were evaluated for their cytotoxic activities against five human cancer cell lines.…”
mentioning
confidence: 99%
“…Structures of the compounds were identified by comparison of their MS and NMR data with those reported in the literature. They were respectively sanguinine ( 1 ) [15], 11-hydroxyvittatine ( 2 ) [16], lycoramine ( 3 ) [17], pancratinine C ( 4 ) [18], homolycorine ( 5 ) [19], hippeastrine ( 6 ) [20], O -demethylhomolycorine N-oxide ( 7 ) [21], zephyranthine ( 8 ) [22], O -methyllycorenine N-oxide ( 9 ) [23], lycoranine C ( 10 ) [24], tazettine ( 11 ) [25], lycorine ( 12 ) [26], 9- O -demethylhomolycorine ( 13 ) [27], homolycorine N-oxide ( 14 ) [23], galanthamine ( 15 ) [28].
Fig.
…”
Section: Resultsmentioning
confidence: 99%